Cochrane Database of Systematic Reviews 2013
DOI: 10.1002/14651858.cd006612.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Homocysteine-lowering interventions for preventing cardiovascular events

Abstract: This updated Cochrane review found no evidence to suggest that homocysteine-lowering interventions in the form of supplements of vitamins B6, B9 or B12 given alone or in combination should be used for preventing cardiovascular events. Furthermore, there is no evidence suggesting that homocysteine-lowering interventions are associated with an increased risk of cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
132
0
17

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 127 publications
(150 citation statements)
references
References 130 publications
1
132
0
17
Order By: Relevance
“…26 Indeed, a substantial body of evidence supports a role of plasma homocysteine in the pathogenesis of hypertension. 27 However, an updated Cochrane review demonstrated that clinical trials using low and high doses of folic acid, vitamin B12, and vitamin B6 had not shown any clinical benefit 28 and claimed that the effects of folate might be influenced by the duration of treatment. 29 The average duration of folic acid supplementation in our study was 2.5 years, which reduced the tHcy level by an average of 6.7 μmol/L (27.92%).…”
Section: Discussionmentioning
confidence: 99%
“…26 Indeed, a substantial body of evidence supports a role of plasma homocysteine in the pathogenesis of hypertension. 27 However, an updated Cochrane review demonstrated that clinical trials using low and high doses of folic acid, vitamin B12, and vitamin B6 had not shown any clinical benefit 28 and claimed that the effects of folate might be influenced by the duration of treatment. 29 The average duration of folic acid supplementation in our study was 2.5 years, which reduced the tHcy level by an average of 6.7 μmol/L (27.92%).…”
Section: Discussionmentioning
confidence: 99%
“…1), are the main precursors of vitamins. Nitrogen status (deprivation, fertilization) or different N sources (ammonia, nitrate) have therefore an impact on the amino acid profile (Scheible et al 2004;Foyer 2010;Marschner 2012). Besides, although the de novo synthesis of purines is tightly regulated, it dynamically varies with developmental and environmental cues (Zrenner et al 2006).…”
Section: Variation In Vitamin Contentsmentioning
confidence: 99%
“…This has led to a number of studies exploring the possible mechanisms by which HHcy may impair vascular function [2,3] and the effects of interventions targeting a lowering of the plasma homocysteine concentration [8]. In contrast, surprisingly little work has been carried out investigating the acute effects of Hcy on cardiac performance during ischaemia reperfusion and on calcium homeostasis and the contractile properties of the individual cardiomyocytes during oxidative stress.…”
Section: Discussionmentioning
confidence: 99%
“…The majority of studies conducted so far have either concentrated on the efficacy of strategies targeting a reduction in plasma Hcy [2,8] or have used vascular endothelial cells, smooth muscle cells, monocytes [2,4] or podocytes [7]. In contrast, the effect of Hcy and HHcy on the myocardium and functional contractile cardiomyocytes has been little studied.…”
Section: Introductionmentioning
confidence: 99%